Application of synthetic-functions expansion to the analysis of antennas and complex platforms - Matekovits, L.; Laza, V.A.; Vecchi, G. (2005 IEEE Antennas and Propagation Society International Symposium, 2005)
SFX (synthetic function expansion) has been shown to effectively handle arrays of unconnected radiators, as well as radiators connected by a beamforming network (BFN); in the case of extended scatterers, the large metal portions need to be cut into different blocks, which requires some extension of the original scheme; this is the subject of this paper.